Multi-scale measurement of high-reflective surfaces by integrating near-field photometric stereo with touch trigger probe. Issue 1 (2020) - Ren, Mingjun; Ren, Jieji; Wang, Xi; Gao, Feng; Zhu, Limin; Yao, Zhenqiang
Abstract: Precision measurement of large scale surface topography is a challenging task for high-reflective parts. This paper presents a multi-sensor system to address this issue by integrating the technical merits of touch trigger probe and photometric stereo. The probe is used to extract a set of high-precision sparse points for an initial surface construction, which is then applied to drive a near-field photometric stereo for recovering dense surface normal of the surface. By fusing the sparse discrete points with the dense surface normal, high-resolution surface topography can be obtained accordingly. Experiments confirm the state-of-the-art performance of the proposed method.